Crop Production - Shafi Nazir; Edited by Elena Bashir and Bantel Robyn (Islamabad National Book Foundation, 2020)
Locally written textbook for agricultural education in Pakistan.
Include Illustrations, Glossary and Index
Keywords: Crop science -- Pakistan -- Textbooks -- Crop science